Learning Strategies Used By The Eighth Grade Olympic Class Students Of MTs Negeri Tanon In 2016/2017 Academic Year - WAHDATI, ROSYIDA TYAS; , Dr. Dwi Harjanti, M. Hum; , Dr. Anam Sutopo, M. Hum (2017)
English has become compulsory subject in Indonesia. It is taught from Elementary up to university. All of the students must learn English in every part of the education level. Unfortunately, some of Indonesian students find it difficult to learn it. They need strategies to master English well. This study was conducted to obtain data on the type of learning strategies used by male and female of the Olympic class students in learning English. The Olympic class is a kind of class which the students are prepared in attending the competition outside the school. In order to get the data, the writer of the study designs a descriptive qualitative research. She chooses the male and the female of the eighth grade of the Olympic class students of MTs Negeri Tanon as the subject of the study. Moreover, to get the data completely and accurately, the writer takes them from interview, questionnaire of SILL, documentation, and observation. Then the writer used oxford language learning strategy to classify the data. The result of the study shows that both of the male and female of the eighth grade of the Olympic class students used the all type of learning strategies proposed by Oxford. They are applied all the strategies of memory strategy, cognitive strategy, compensation strategy, meta-cognitive strategy, affective strategy and social strategy. But there are differences in the frequency of the using, and the preference of the using. The female likes to use the strategy from higher to lower: metacognitive, compensation, cognitive, affective, memory, and social strategy. While the male of the eighth grade of the Olympic class from higher and lower: metacognitive, cognitive, affective, compensation, memory, and social strategy. Hopefully, the research finding can be used by the teacher to give knowledge about learning strategies and the students to use the appropriate learning strategies so that they will enjoy learning English, and as the result they will get the best achievement in English.